Learning culture in a Chinese SME: the unique role of work-family enrichment. Issue 2 (29th November 2019) - Xie, Lei; Dirani, Khalil M.; Beyerlein, Michael; Qiu, Shaoping
Abstract : Purpose: Learning and development are critical to a business's success. This paper aims to focus on organizational factors at multiple organizational levels that facilitate learning culture in a small- and medium-sized enterprise (SME) in northwestern China. Design/methodology/approach: This study is qualitative in nature. A single case study method is used to explore an SME's organizational factors that facilitate learning culture. Findings: This paper categorizes the organizational factors into seven dimensions: shared vision, creating continuous learning opportunities, informal learning that promotes inquiry and dialogue, collaboration and team learning, knowledge management systems, work–family enrichment and encouragement and support. This paper also compares the findings with learning culture models from Western research. Research limitations/implications: Chinese culture has far-reaching and fundamental effects on many East Asian countries and regions. For SMEs in similar cultural settings with a collectivist orientation, future research may focus on the effect of the work–family enrichment on learning culture. Originality/value: Work–family enrichment was found to be an important factor that influences learning effectiveness in this Chinese small business based on traditional values in Chinese culture.